Expression of LHCG receptor in the human vulva - Zirnask, Helen; Pöllänen, Pasi; Suutre, Siim; Torga, Taavi; Rüsse, Samuel; Salumäe, Liis; Kotsar, Andres; Kokk, Kersti (Taylor & Francis, 2026)
Background
Elevated serum LH levels have been identified in both men and women between the ages of 40 and 70. In previous studies LHCG receptor was detected in the mouse and human penis both in corpus cavernosum penis and corpus spongiosum penis and in the mouse vulva. There is no information about the expression of LHCG receptor in the human vulva up to now. The aim of this study is to examine the expression of the LHCG receptor in the human vulvar tissue to determine whether LH could have an effect on the vulva.
Materials and methods
Vulva tissue was obtained from three patients (ages 68, 76 and 71) undergoing surgery due to squamous cell carcinoma of the vulva. Immunohistochemistry was used for the detection of the LHCG receptor.
Results
Positive immunoreaction for LHCG receptor was detected in the different cell types of the human vulva.
Conclusions
This study provides clear evidence of LHCG receptor expression in various cell types within the human vulva. These findings reinforce the idea that elevated postmenopausal gonadotropin levels may directly impact vulvar tissue. Further studies are indicated.